THE EFFECT OF THE GLOBAL RECESSION THREAT ON INDONESIAN IMMIGRATION POLICY REGARDING COUNTRIES WITH VISIT VISA-FREE SUBJECT - Muhammad Rifkie Aditama; Ni Putu Ayu Y.D.L; Norbertus Oriwardana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The weakening global economic contraction was triggered by weakening consumption activity, international trade, and investment. This is in line with the Covid-19 pandemic that hit various parts of the world, especially Indonesia. A weakened global movement that causes multidimensional crises impacts state systems. The purpose of this study is to examine the steps of the Indonesian government in dealing with global threats regarding immigration policies regarding the subject of visa-free countries. The research method used is normative analysis, where the data is obtained based on an in-depth analysis of the literature study. This study aims to get information on the Indonesian government's strategy, especially in Immigration, to determine preventive measures for a visa-free visit policy against the threat of a global recession during the Covid-19 Pandemic. Keywords: Economic Contraction, Global Recession, Free Visit Visa